Coumarins - fast synthesis by the knoevenagel condensation under microwave irradiation / Rahmat Mohamed Tahir - Mohamed Tahir, Rahmat (2008)
Coumarin nowadays is of great importance especially in the area of pharmaceutical. Therefore, a faster way of producing coumarin was needed while maintaining the purity and yields of product as high as possible. One of the methods is Knoevenagel condensation under microwave assisted irradiation. This research was aimed to prove that under the microwave irradiation the Knoevenagel condensation can be successfully applied to the synthesis of a number of coumarins. Also, the researcher wanted to find the most suitable base for this reaction. 2-hydroxy-4-methoxy benzaldehyde and 2- hydroxy-5-methoxy benzaldehyde were reacted with diethyl melonate in the presence of three different bases; diethylamine, pyridine, and potassium tert-butoxide for three different reactions. The reactions were set under different conditions: stirring with no heating for six hours; stirring with heating at 80°C for six hours; and under microwave assisted irradiation at 1000 watt power, 70°C, and stirring speed of I 00 rpm for one hour. TLC was used to prove the reactions were completed. To confirm the structure of coumarins (13 and 16) formed, 1H and 13C-NMR analyses were used. From the results, it was found out that diethylamine was the most suitable base for this reaction therefore used throughout the research. Productions of coumarins were significantly increased from stirring, no heating condition (29.07 % and 61.13 %) to stirring, heating condition (39.52 % and 68.23 %) to microwave assisted irradiation (48.39 % and 84.68 %). The time for reaction under microwave condition was also decreased to one hour and yet the percentage yield was still maintained.